Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

Does anyone know how to solve [1+tan(2)x / tan(2)x]=csc(2)x?

3 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    The equation is not quite clear. I suppose that you mean this:

    [1 + tan(2x)] / [tan(2x)] = csc(2x)

    If yes, then

    cotg(2x) + 1 = csc(2x)

    cos(2x) + sin(2x) = 1

    (√2) sin(2x + π/4) = 1

    sin(2x + π/4) = √2/2

    2x + π/4 = arcsin(√2/2)

    Solutions are

    x = πn

    and

    x = π/4 + πn

    where n is any whole number.

    -

    Note: To square both sides of an equation is not a correct way. It gives additional false results.

    -

  • ted s
    Lv 7
    1 decade ago

    If the (2) was to mean squared then your statement is an identity, cot^2( x )+ 1 =

    csc^2 (x). If it meant 2x then it can be written as cos x + sin x = 1. Square both sides ,clean it up, you find sin(4x) = 0 which has answers n(pi / 4) , n = 0,1,2,3,4,5,6,7 for answers in [0,2 pi)

  • 1 decade ago

    [ 1 + tan(2)x / tan(2)x ] = csc(2)x

    we have : tan2x = sin2x / cos2x

    we have

    1 +tan2x =( csc2x)(tan2x) = (1 /sin2x)(sin2x / (cos2x)

    1 +tan2x = 1 / cos2x

    cos2x( 1 +tan2x ) = 1

    cos2x + (tan2x) (cos2x) = 1

    cos2x +[( sin2x / cos2x)(cos2x)] = 1

    cos2x + sin2x = 1

    we have ( csc2x = ( 1 / sin2x) =( csc2x) ( sin2x) = 1

    we have

    cos2x + sin2x =( csc2x) (sin2x)

    we have

    csc2x = [( cos2x + sin2x ) / sin2x ]

    = (cos2x / sin2x) + (sin2x /sin2x)

    but ( cot (2x )= ( cos2x / sin2x)

    csc2x = cot 2x + 1

    but ; cot 2x = 1 / tan2x

    csc2x = ( 1 / tan2x) + 1

    csc2x = (1 + tan2x) / tan2x =

    (1 + tan2x ) / tan2x = csc2x

Still have questions? Get your answers by asking now.